Effects of Self-Control on Subjective Well-Being: Examining the Moderating Role of Trait and State Motivation - Zhao, Guojun; Xie, Fusen; Luo, Yuchen; Liu, Yixuan; Chong, Yuan; Zhang, Qi; Wang, Wenjie (Frontiers in Psychology, 2022)
It is well documented that self-control has a positive effect on individuals’ subjective well-being. However, little research has focused on the moderators underlying this relationship. The present research used two studies to examine the moderating role of both trait and state motivation on the relationship between self-control and subjective well-being using psychometric and experimental models, respectively. In Study 1, we explored whether trait motivation (including promotion vs. prevention motivation) moderated the relationship between trait self-control and subjective well-being using a psychometric model. In Study 2, we examined the moderating effects of both trait and state motivation on the effect of state self-control (measured via ego depletion) on subjective well-being using an experimental model. Our results indicated that self-control had a positive effect on subjective well-being, with this relationship being primarily moderated by prevention motivation. When state and trait prevention motivations were congruent, self-control had the most obvious impact on subjective well-being. This study suggests that current understandings around the association between self-control and happiness is limited, implying that motivation should be the focus of future research.